KINERJA MOTOR INDUKSI PASCA PENGGANTIAN BUSBAR ROTOR ALUMINIUM MENJADI TEMBAGA UNTUK MEMENUHI KEBUTUHAN RATING DAYA AWAL - Ramli Adi Putra; Chairul G. Irianto (Website, 2016)
Replacement of aluminum busbar into a copper busbar can be a solution to repair a squirrel cage rotor. Due to resistance value of copper is 2/3 smaller than the resistance of aluminum, the current density in copper busbar becomes smaller so that the increase in rotor temperature becomes lower. With the expansion rate of the copper busbar material is smaller then the heat rise in the bearings and rotor shaft becomes smaller so that friction and vibration motor becomes lower. The first step for the replacement of the aluminum to copper busbar rotor, starting with testing the damage busbar using growler tool to find out which busbars are broken and not in the rotor. Once the disconnected busbar is known the aluminum is released from the rotor frame by using sodium hydroxide (NaOH) to dissolve the aluminum material. To replace the aluminum to copper busbar, size and thickness of the copper busbar cross-section should not be the same as the aluminum busbar, it can be 60% for aluminum and 40% for copper. Replacement of aluminum to copper busbar does not change the value of the reactance of the rotor. After the busbar replacement, the megger tests show a good value, Polarization Index (PI) value is greater than 2.0. The no-load test indicates that the current in the winding phases of the R-S, R-Q and S-T does not exceed 5%, the value of the vibration testing does not exceed 2.8 mm / s, and the value of the test results surge chart shows a good standard.Penggantian busbar aluminium menjadi tembaga merupakan solusi untuk perbaikan rotor sangkar tupai.Karena nilai resistansi tembaga adalah 2/3 lebih kecil dibandingkan dengan resistansi aluminium maka rapat arus di busbar tembaga menjadi lebih kecil sehingga kenaikan temperatur di rotor menjadi lebih rendah. Dengan tingkat pemuaian bahan busbar tembaga yang lebih kecil maka kenaikan panas di bantalan dan poros rotor menjadi lebih kecil sehingga gesekan dan getaran motor menjadi lebih rendah. Langkah pertama untuk penggantian busbar rotor aluminium menjadi tembaga, diawali pengujian kerusakaan busbar dengan menggunakan alat growler untuk mengetahui busbar mana yang terputus dan busbar yang tidak terputus. Setelah diketahui busbar yang terputus, busbar aluminium dilepaskan dari rangka rotor dengan menggunakan zat kimia natrium hidroksida (NaOH) untuk melarutkan bahan aluminium.Untuk mengganti busbar aluminium menjadi tembaga, ukuran besar dan tebal penampang busbar tembaga tidak harus sama dengan aluminium, dapat berbanding 60% untuk aluminium dan 40% untuk tembaga. Penggantian busbar aluminium menjadi tembaga tidak mengubah nilai reaktansi rotor. Setelah penggantian busbar, hasil pengujian megger menunjukkan nilai standar yang baik, nilai Indeks Polarisasi (IP) lebih besar dari 2,0. Berdasarkan hasil pengujian beban nol untuk arus pada belitan fase-fase dari R-S, R-T dan S-T tidak melebihi 5%, nilai hasil pengujian getaran tidak melebihi 2,8 mm/s, dan nilai hasil pengujian surge menunjukkan grafik standar yang baik.